INDONESIAN STUDENTS’ AND TEACHERS’ PERCEPTION OF GOOD EFL TEACHER’S CHARACTERISTICS - Eka Uliyanti Putri; Yimmy Yimmy; Ria Antika (Universitas Pamulang, 2022)
This research is aimed at knowing the results from the students’ perception regarding the good characteristics teacher whether English teachers have fulfilled the good teacher characteristic and also knowing the teacher’s view on the characteristics of being good EFL teacher. This research also aims at providing anyone concerned with ELF learning and teaching process, with a much better view so that there will be a more understanding toward the ideal figure that should be possessed by the teacher. This research is conducted in into a few subjects ( 7 EFL teacher and approximately 80 students) in a certain time or period thus the result will just represent the point of view of the students and their teacher in that specific time. Since survey research requires large amount of data. The research was conducted in Global Institute and Polytechnic LP3I tangerang. The researchers use two questionnaire to gain the data. This research has purpose that teachers could know their students perception and opinions about themselves. The result shows that teachers must have four aspects, they are technical knowledge, pedagogical skills, personal and interpersonal skills. So, the teachers can implement those aspects to encourage students to get involved in teaching learning process